Badania Niektórych Skał Krajowych Metodą Trójosiowego Ściskania - Supeł, J.; Zawada, J. (Engineering Transactions, 1972)
Four types of Polish rocks subject to three-dimensional compression are investigated. The paper describes the construction and application of a special pressure device designed for that purpose. The experimental results obtained, enabling us to determine the values of material constants (angle of internal friction and cohesion), are presented in the form of the co-called “limit curves” on the plane of Mohr circles.